STUDY OF SURFACE FINISH AS A FUNCTION OF CERAMIC TOOL WEAR WHEN TURNING HARDENED AISI 52100 STEEL - Cescon Pereira, Jean Carlo; Pereira, Vinícius Chiaradia (International Journal of Engineering Technologies and Management Research, 2025)
The turning process in hard materials has been way more used in the last few years because of the demand to reduce the manufacturing cost. This research analyzes the superficial roughness evolution in mixed ceramic tool`s wear used to turn ABNT 52100 hardened steel. This study has the objective to find the major reasons that influence the flank wear in ceramic insert and analyze how this wear influences the samples superficial roughness. In the turning process the variables cutting speed (Vc), feed (f) and machining depth (ap) were changed during the tests and analyzed their influences in superficial roughness. The experiments show that the greatest tool`s wear, for the variables used, was because of the forward speed. In the superficial finish study the only thing which has a great impact in average roughness (Ra) was the forward speed that when elevated has increased the average roughness. Meanwhile the vibration excess, caused by the machine`s low hardness, mainly for the several cutting properties, caused damages to the cutting tool that helped to increase the roughness rate while the flank wear also advanced.